1993
DOI: 10.1002/adma.19930050704
|View full text |Cite
|
Sign up to set email alerts
|

Optical Nonlinearity:Phenomena, applications, and materials

Abstract: Rectification, inversion, modulation, harmonic generation, and heterodyning are all effects well known in the world of electronics as the essential properties of practical devices. These, and many other, related, effects have applications in optics, made possible by te development of the laser, a source of intense monochromatic light. In this article, from the viewpoint of the materials scientist, the basic phenomena and their applications are presented before and various materials in use in nonlinear optics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
102
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(107 citation statements)
references
References 210 publications
2
102
0
Order By: Relevance
“…The calculated FOM of CBOB is 1.232 while d ij % d eff with a theoretical estimation. By the comparisons with the available experiment data of b-BBO and LBO crystals [16], it is found that the FOM of CBOB is larger than those of b-BBO and LBO crystals.…”
Section: Calculations Of Susceptibilitiesmentioning
confidence: 91%
See 2 more Smart Citations
“…The calculated FOM of CBOB is 1.232 while d ij % d eff with a theoretical estimation. By the comparisons with the available experiment data of b-BBO and LBO crystals [16], it is found that the FOM of CBOB is larger than those of b-BBO and LBO crystals.…”
Section: Calculations Of Susceptibilitiesmentioning
confidence: 91%
“…In short, large frequency-doubling coefficients and figure of merit (FOM) are essentials for NLO material applications. They depend on the inherent nature of the material, in which the FOM value is proportional to the square of the SHG effective coefficient and inversely proportional to about cube of the refractive index ðFOM ¼ d 2 eff =n 2 o n 2o Þ [16]. Now, the understanding of the material structure characteristics relating with the NLO mechanisms has been considerably improved.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The structural flexibility of organic chromophores easily modifiable through precise chemical syntheses in view to increase the molecular hyperpolarizability b (ijk) and the possible grafting of chirality centers are remarkable assets compared to the difficulties of the engineering route of inorganic materials in which the requirements of noncentrosymmetry and high susceptibilities w (2) have to be accounted at crystal [3,4]. An essential condition to realize even-order NLO processes in materials is a noncentrosymmetric structure; however, optimal molecular orientations are required if appreciable effects are to be achieved in molecular materials [5,6]. Organic nonlinear chromophores of fast optical responses to the laser light have encouraged the research of highly efficient organic materials.…”
Section: Introductionmentioning
confidence: 99%
“…[ 26,27 ] Computer generated holography technique is utilized to design gold-fork microstructure with desired topological charge, which is then fabricated on gold coated quartz substrate using focus ion beam (FIB) technique. Both second and third harmonic generations of optical vortices are experimentally observed in the polymer thin fi lm/gold-fork/ quartz composite device.…”
mentioning
confidence: 99%